1995
DOI: 10.1096/fasebj.9.9.7601344
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms by which extremely low frequency magnetic fields affect opioid function

Abstract: Although extremely low frequency (ELF, < 300 Hz) magnetic fields exert a variety of biological effects, the magnetic field sensing/transduction mechanism (or mechanisms) remain to be identified. Using the well-defined inhibitory effects that magnetic fields have on opioid peptide mediated antinociception or "analgesia" in the land snail Cepaea nemoralis, we show that these actions only occur for certain frequency and amplitude combinations of time-varying sinusoidal magnetic fields in a manner consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
76
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 38 publications
(86 reference statements)
8
76
0
2
Order By: Relevance
“…Existing TMS protocols for the treatment of pain in FM differ in frequency (nearly always pulsed), intensity, duration, and setting [28][29][30][31]; no standardized protocol for ELF-MF treatment in FM has been developed, and there are no studies in this area with respect to total body stimulation with the magnetic mattress. Consistent with similar studies, our results demonstrate an analgesic and antinociceptive effect, similar to the opioid analgesic effect in PEMFexposed patients [39][40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Existing TMS protocols for the treatment of pain in FM differ in frequency (nearly always pulsed), intensity, duration, and setting [28][29][30][31]; no standardized protocol for ELF-MF treatment in FM has been developed, and there are no studies in this area with respect to total body stimulation with the magnetic mattress. Consistent with similar studies, our results demonstrate an analgesic and antinociceptive effect, similar to the opioid analgesic effect in PEMFexposed patients [39][40].…”
Section: Discussionsupporting
confidence: 93%
“…However, the source of sensory input in FM patients remains unknown; thus, the duration of the efficacy of ELF-MF remains undetermined. Similarly, the magnetite hypothesis, based on the induction of electric currents, appears to be an unlikely mechanism, given that the induced fields are orders of magnitude lower than the endogenous electric fields in tissues; a connection between magnetite and the nervous system has not been demonstrated [39][40]47].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects on SIA induced by the -metal exposure is similar to that observed following exposure to various exogenous magnetic fields in mice and other species (Ossenkopp et al 1985;Kavaliers & Ossenkopp 1986, 1988a,b, 1991Betancur et al 1994;Ghione et al 1994;Del Seppia et al 1995Papi et al 1995;Prato et al 1995Prato et al , 1996aSartucci et al 1997). Those studies showed that the effect of artificial magnetic fields on SIA is similar to that obtained after administration of the prototypic opiate antagonist naloxone, supporting an inhibitory effect of various magnetic fields on opioid-mediated responses.…”
Section: Discussionsupporting
confidence: 57%
“…Magnetic fields have been proposed to alter the proprieties and stability of biological membranes, their transport characteristics, and the intra-and extracellular distribution and flux of calcium ions. Results of a number of investigations have shown that the inhibitory effects of magnetic fields on opioid analgesia in snails involve alterations in the functioning of calcium and/or flux of calcium ions , 1991 consistent with a resonance model (Prato et al 1995), as well as alterations in protein kinase C-associated and nitric oxide and nitric oxide synthase-related transduction mechanisms Kavaliers & Prato 1999;Prato et al 2000). The absence of magnetic field influencing biological systems following similar mechanisms remains to be determined, although Lednev et al (1996) suggested that effects seen at near-zero (vector-nulled) magnetic field conditions are related to the parametric resonance model.…”
Section: Discussionmentioning
confidence: 73%
“…The changes in power EEG bands of control, for both skull and brain, were approximately similar with changes in power spectrum of recovery (compare Figures 2(a), (c) and Figures 3(a), (c)). Thus, the present EEG power spectrum findings are much consistence with previous studies [1,3,[14][15][16][17] which had been reported that ELF-MF affect significantly the brain electrical activity. They indicated that constant magnetic filed affects primarily Ca 2+ or, alternatively, K + -dependant biochemical reactions known to play key functions in regulation of the cellular activity; in particular, morphine-induced changes in cell functions.…”
Section: Discussionsupporting
confidence: 92%